THE ASPECT FROM THE HISTORY OF MEDICINE: LATIN BOTANICAL NAMES OF MEDICINAL PLANTS AND THEIR PROPERTIES - Ivanova, Tetiana (European Science, 2023)
The article discusses the role of plants and their properties used in medicine and pharmacy, production of the necessary medicines and their use in the treatment of people